2015
DOI: 10.1002/asi.23528
|View full text |Cite
|
Sign up to set email alerts
|

The construction of interdisciplinarity: The development of the knowledge base and programmatic focus of the journal ClimaticChange, 1977–2013

Abstract: Climate change as a complex physical and social issue has gained increasing attention in the natural as well as the social sciences. Climate change research has become more interdisciplinary and even transdisciplinary as a typical Mode‐2 science that is also dependent on an application context for its further development. We propose to approach interdisciplinarity as a co‐construction of the knowledge base in the reference patterns and the programmatic focus in the editorials in the core journal of the climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this research, the Science Citation Index Expanded (SCIE) and Social Science Citation Index (SSCI) are used to search for scientific publications in the WoS database. The keywords including "climate chang*", "climate variabilit*", "global warming", and "climate warming" present in the title or abstract are retrieved (Haunschild, Bornmann, & Marx, 2016;Li, Wang, & Ho, 2011;Wang et al, 2014). The time span of data is confined to 2001-2021, and the document types is limited to article and review.…”
Section: Data and Methods Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the Science Citation Index Expanded (SCIE) and Social Science Citation Index (SSCI) are used to search for scientific publications in the WoS database. The keywords including "climate chang*", "climate variabilit*", "global warming", and "climate warming" present in the title or abstract are retrieved (Haunschild, Bornmann, & Marx, 2016;Li, Wang, & Ho, 2011;Wang et al, 2014). The time span of data is confined to 2001-2021, and the document types is limited to article and review.…”
Section: Data and Methods Data Collectionmentioning
confidence: 99%
“…Climate change is a typical interdisciplinary research field with characteristics of complexity, variety, and comprehensiveness, requiring the integration of knowledge from social sciences, natural sciences, engineering, and technology (Bhaskar et al, 2010; Hellsten & Leydesdorff, 2016; McCright et al, 2013). It is also a global issue that affects the survival and development of humanity.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, some researchers and journals in the LIS have started to pay attention to climate change in recent years. Hellsten and Leydesdorff (2016) explored the construction of interdisciplinarity, including the knowledge base and programmatic focus, in the core journal of the climate change sciences— Climate Change . Their results showed that the widening of the knowledge base was important in this field, and the programmatic focus followed policy-oriented issues and incorporated public metaphors.…”
Section: Literature Reviewmentioning
confidence: 99%